ANALISIS ANTRIAN PELAYANAN NASABAH PADA PT BANK SYARIAH MANDIRI CABANG BUNGKU - HILDA, HILDA (Fakultas Ekonomi Universitas Tadulako, 2018)
This study aims to analiyzethe system of optimal service queue at the teller that existed in PT BankSyariah Mandiri Bungku Branch. The analytical method used is M/M/1 or single channel singlephase, but to compare the optimal or not the queue of customer service at PT Bank Syariah Mandiribranch when adding one teller in solid time so the used M/M/S analysis method or multi channelsingle phase. The result of analysis by using one teller in cash deposit of solid time is probability insystem is equal to 0,0572. The teller utility level is 0,94 or 94 % the average number of customers inthe system is 17 people, while using two tellers can be seen the probability in the system is 0,350 or noone in the system. Teller utility rate is reduced to 0,48 or 48% of the average number of customers inthe system is 1 person, it indicates that the customer queuing in the system is optimal. Based on thedata is can be concluded that the addition of one teller at a solid time can optimize the existingservices in PT Bnk Syariah Mandiri Bungku branc.